Design and analysis of a hydraulic drive downhole traction in-pipe robot based on flexible support structure. (January 2021) - Shang, Jianzhong; Fang, Delei; Luo, Zirong; Wang, Rong; Li, Xin; Yang, Junhong
For the strict requirement of convey tools in horizontal well operation, this paper proposes a hydraulic drive downhole traction in-pipe robot based on the flexible support structure, which has the characteristics of compact structure, large traction force, and high reliability. Based on the design of mechanical structure, the motion principle of the robot continuous propulsion is analyzed. Analysis of mechanical characteristics of the flexible support structure is obtained. Hydraulic system including some key hydraulic components are designed and analyzed. Control strategy of purely hydraulic drive mode is researched. Simulation analysis and experimental platform are all accomplished to prove feasibility of purely hydraulic drive mode, and some parameters that affect the robot performance are discussed. Results show that the novel in-pipe robot has a total length of 3.4 m and can adapt to borehole diameter of 155–218 mm. When load is 15 kN, robot motion speed reaches 0.12 m/s. What is more, this novel traction robot does not require an electric power source and has great advantages in safety and reliability, which shows considerable potential for the downhole operation.